2006
DOI: 10.1243/09544054jem578
|View full text |Cite
|
Sign up to set email alerts
|

The development of nickel-tungsten carbide functionally graded materials by a laser-based direct metal deposition process for industrial slurry erosion applications

Abstract: Functionally graded materials (FGMs) consisting of Ni-tung (nickel-tungsten carbide) powders with different concentrations of tungsten carbide particles are successfully deposited by a laser-based direct metal deposition (LBDMD) process on 4140 steel substrates. The slurry erosion behaviour of the Ni-tung FGMs is studied at different impingement angles. The slurry erosion tests are performed at Southern Methodist University's Center for Laser-Aided Manufacturing using a centrifugal-force-driven erosiontesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…[2,3] Tucker et al [4] have shown that the slurry erosion resistance of mixed-particle laser-clad overlays is superior to that of precipitation-hardened alloys. Yarrapareddy et al [5] demonstrated the superior slurry wear properties of nickel-tungsten functionally graded materials developed by laser cladding. Chattopadhyay [6] found excellent erosion resistance in a Stellite 6 plasmawelded overlay on cast-ferritic stainless steel (CA6NM) that is used as a turbine runner material.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Tucker et al [4] have shown that the slurry erosion resistance of mixed-particle laser-clad overlays is superior to that of precipitation-hardened alloys. Yarrapareddy et al [5] demonstrated the superior slurry wear properties of nickel-tungsten functionally graded materials developed by laser cladding. Chattopadhyay [6] found excellent erosion resistance in a Stellite 6 plasmawelded overlay on cast-ferritic stainless steel (CA6NM) that is used as a turbine runner material.…”
Section: Introductionmentioning
confidence: 99%
“…Tucker et al [10] have shown that the slurry erosion resistance of mixed-particle laser-clad overlays is superior to that of precipitation-hardened alloys. Yarrapareddy et al [11] reported superior slurry wear properties of nickel-tungsten functionally graded materials developed by a laser deposition. Among hardfacing alloys, commercial Co-based Stellite 6 and Ni-based Colmonoy 88 powder are unique alloys that contain mixed chromium tungsten borides and carbides for maximum abrasion and corrosion resistance and also relatively low cost alloys.…”
Section: Introductionmentioning
confidence: 99%
“…FGMs are superior to monolithic or homogeneous materials for many applications such as armor [3], thermal barrier coatings (TBC) [4], slurry erosion resistant surfaces [5], and thermo and pyro-electric devices [6][7][8]. FGMs are usually prepared by the powder metallurgy technique [3,6,9].…”
Section: Introductionmentioning
confidence: 99%
“…Sabatello et al [2] have fabricated graded TiC-based cermets by infiltration of porous ceramic preform with molten metal. Using laser-based direct material deposition, Yarrapareddy et al [5] have deposited an FGM consisting of Ni and WC powders on AISI 4140 steel plate. The FGM had a high percentage of discrete WC particles in a Ni matrix, with the percentage of WC varying in each layer of the deposit [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation